"He Needs to Talk!": A Chaplain's Case Study of Nonreligious Spiritual Care. Issue 1 (2nd January 2016) - Nolan, Steve
Abstract : Chaplains have always worked with nonreligious people, but it is not always clear what is distinctive about their contribution. This case describes an episode of nonreligious spiritual care in order to explore the value of chaplaincy work with people who regard themselves as nonreligious. This case reports on work with a dying man and his family—wife, daughter, sister, and son-in-law—whose religion is secularized, but whose secularism is touched by the sacred.